ANALISIS TERHADAP TINDAK PIDANA KORUPSI PENYALAHGUNAAN KEWENANGAN OLEH KEPALA DESA PADA PUTUSAN PENGADILAN TINDAK PIDANA KORUPSI SEMARANG NO. 21/ PID.SUS/2013/ PN.TIPIKOR.SMG - FAWZI, HABRAHAM OKKY (Dinamika Hukum, 2017)
The purpose of this study is to: 1) Analyze implementation of the criminal law against the crime of corruption misuse of authority by the head of the village on the Court ruling criminal act Corruption Semarang No. 21/Pid. Sus/2013/PN. TIPIKOR. Smg. 2) Analyze consideration of the law judge in meting out the verdict against corruption a criminal offence of abuse of authority by the head of the village on the Court ruling criminal act Corruption Semarang No. 21/Pid. Sus/2013/Pn. Tipikor.Smg. The method of approach in writing this is the juridical normative. The specification of this research uses descriptive analytic. Data source using secondary data. Data collection technique using the study of librarianship and study documents. To analyze the data, the researchers used a qualitative normative method. Based on the research results obtained conclusions that: 1) Application of criminal law in the Crime of Corruption Abuse of Authority by the head of the village on the Court ruling criminal act Corruption Semarang No. 21/Pid. Sus/2013/PN. Tipikor. Smg has been appropriate and in terms of the application of criminal law materially deeds accused BUDIYONO, St. bin HADI SUWONO meet elements of the indictment as subsidair delik chosen by an Assembly of Judges stating that the defendant is proven guilty of the crime of corruption set in article 3 of ACT No. 20 of 2001 about the changes to the Act No. 31 of 1999 regarding the eradication of criminal acts of corruption. 2) in taking its decision, the Tribunal judge do the Juridical reasoning based on facts obtained from the trial indictment the Prosecutor, witnesses, expert information, evidence, description of the defendant and others. In addition the Tribunal judges also perform non-juridical considerations based on the background of the defendant, as a result of the defendant's deed, as well as a condition or capability of irresponsible defendant. However, according to the author of the judge was supposed to dig in-depth on a non-juridical considerations primarily about things that are incriminating the accused. Keywords: Criminal Acts of Corruption, Abuse of Authority